Предмет: Алгебра,
автор: slava626
Нужна помощь (9^2x)-2*(9^x)-3=0
Ответы
Автор ответа:
0
( 9 ^ 2х ) - 2 * ( 9 ^ Х ) - 3 = 0
9 ^ Х = А ; А > 0
а^2 - 2а - 3 = 0
D = 4 + 12 = 16 ; V D = 4
A1 = ( 2 + 4 ) : 2 = 3
A2 = ( 2 - 4 ) : 2 = - 1 ( < 0 )
9 ^ X = 3
3 ^ 2x = 3
2x = 1
X = 0,5
9 ^ Х = А ; А > 0
а^2 - 2а - 3 = 0
D = 4 + 12 = 16 ; V D = 4
A1 = ( 2 + 4 ) : 2 = 3
A2 = ( 2 - 4 ) : 2 = - 1 ( < 0 )
9 ^ X = 3
3 ^ 2x = 3
2x = 1
X = 0,5
Похожие вопросы
Предмет: Математика,
автор: daradobos006
Предмет: Физика,
автор: Аноним
Предмет: Другие предметы,
автор: Nika228anna228
Предмет: Алгебра,
автор: Lalechka
Предмет: Математика,
автор: Ксенька111